The Effect of Rondo Games Training on Passing Accuracy in Football Games - Puji Wibowo; Nurhidayat, Nurhidayat (Fair Play, 2024)
The background to this research is based on the passing ability of SSB Rajawali Semarang players which is lacking and still needs to be improved as well as variations in training to improve passing techniques and the lack of passing accuracy. The aim of this research was to determine the effect of rondo games training on passing accuracy. This research is an experiment with quantitative methods and uses a "one group pretest-posttest design". Population of 20 SSB Rajawali Semarang players using purposive sampling technique. The test instrument uses the short pass instrument developed by Bobby Charlton (2012 :3) with a validity of 0.653 and a reliability of 0.879. The results of the rondo games practice data analysis showed an average pretest of 232.50 and posttest of 315.00 and the average difference between the pretest and posttest of the rondo games practice group was -82,500 with sig.(2-tailed) = 0.000. There was a difference in the increase in passing accuracy of SSB Rajawali players between before and after being given rondo games practice. The conclusion from this research was that there was an increase between before and after being given treatment through rondo games training towards increasing the passing accuracy of SSB Rajawali Semarang players. Suggestions for coaches could be to use this exercise as a variation of passing practice to improve basic passing technical skills.